MEMBANGUN PASTORAL KONTEMPLATIF BAGI GENERASI Z YANG TERJEBAK DALAM ISU FEAR OF MISSING OUT (FOMO): Pastoral - Frisilia Jesika Sumangkut; Vera E. Burhan (Jurnal Pelayanan Pastoral, 2026)
Generation Z lives within a digital environment characterized by rapid information flows, limitless connectivity, and the dominance of social media in shaping identity. This reality gives rise to the phenomenon of Fear of Missing Out (FOMO), defined as anxiety experienced when individuals feel left behind from socially valued experiences. In the context of church life, FOMO not only affects psychological well-being but also diminishes the quality of spiritual growth among young people. This study aims to formulate a contemplative pastoral model as a church response in accompanying Generation Z experiencing FOMO-related pressures. The research employs a qualitative approach within the framework of practical theology, utilizing in-depth interviews with eight active young church participants in Manado, as well as a literature review. Data analysis was conducted thematically through stages of reduction, categorization, and theological interpretation. The findings reveal four main pillars of the contemplative pastoral model: (1) a culture of silence, (2) authentic personal accompaniment, (3) a non-competitive community, and (4) the formation of sustainable spiritual disciplines. This model is relevant as a pastoral approach to restoring the spiritual depth of Generation Z amid the pressures of digital culture.